A cantilever-type vibro-impact triboelectric energy harvester for wind energy harvesting. (1st September 2022) - Zhao, Chaoyang; Hu, Guobiao; Yang, Yaowen
Highlights: A novel cantilever structure is proposed for galloping energy harvesting based on the triboelectric mechanism. An aero-electro-mechanical model is formulated to investigate the dynamics of the harvester. Effects of the system parameters on the energy harvesting performance are comprehensively analyzed. The developed aero-electro-mechanical model is experimentally validated. Abstract: This paper presents a novel wind energy harvester utilizing galloping effect coupled with triboelectric-based energy conversion to convert the flow-induced structural vibration into electricity. The proposed harvester comprises a host cantilever beam, a stopper, and a middle plate with one rotation degree of freedom. The triboelectric layers and electrodes are placed in between the surface of the stopper and middle plate. A bluff body is fixed at the free end of the host beam to induce galloping vibration, which drives the middle plate to contact with the stopper periodically, thus generating electricity due to the triboelectric-based conversion mechanism. The proposed harvester can harness energy from wind velocity as low as 2 m/s depending on the selection of cantilever beams. A distributed coupled aero-electro-mechanical model is formulated to investigate the dynamic behavior of the harvester. The impact between the middle plate and stopper is found to have a significant influence on the energy generation performance of the harvester. Rigid impact could cause irregular and impulsive separation of contact surfaces, leading to sporadic voltage output. An optimal configuration is determined by selecting proper parameters of the stopper, bluff body, and gap distance in the design of the harvester. The proposed model shows good accuracy for modeling a moderate impact-engaged triboelectric harvester working on contact and separation mode. The fabricated harvester prototypes can produce a root mean square voltage of 12.8 V with a maximum power of 290 µW at wind velocity of 10 m/s. Even at low wind velocity, such as 6 m/s, the maximum power can reach up to 196 µW, demonstrating the promising energy scavenging capability of the proposed harvester.